Numerical analysis of modal and flexural behavior of nanocomposite adhesively bonded joints - Hulagu, Burak; Acar, Volkan; Çakır, Ferit; Akbulut, Hamit (Springer Heidelberg, 2025)
This study presents a detailed numerical and experimental investigation into the modal and flexural behaviors of nanocomposite adhesively bonded joints, specifically aluminum 2024 T3 adherents bonded with DP270 adhesive, reinforced with graphene nanoparticles. Initially, a finite element model was developed for the double strap joint (DSJ) to determine its modal properties, and the results were solved using MATLAB. These results were closely aligned with those obtained from both ANSYS simulations and experimental data. Building on this validation, other joint types were analyzed using finite element methods, eliminating the need for additional experiments. The study compared the modal and flexural behaviors of various joint configurations, with particular attention to the influence of graphene reinforcement. Among the configurations, DSJ and tapered double strap joint (TSJ) exhibited the highest stiffness and load-bearing capacity. The findings suggest that graphene nanoparticles significantly enhance the mechanical performance of the joints, offering valuable insights for various engineering applications.
Keywords: Finite element; Adhesively bonded joints; Vibration; Mechanical testing; Graphene